Billy the Kid: a reader's guide - Etulain, Richard W. (University of Oklahoma Press, 2020)
"A companion book to Richard W. Etulain's Thunder in the West, it summarizes and evaluates more than a century of the interpretations of Billy the Kid, including biographies, histories, novels, and movies, as well as major archival sources and research collections."--